A comparison of external and internal maxilla and mandible morphology of water bugs (Hemiptera: Heteroptera: Nepomorpha) - Brożek, Jolanta (Zootaxa, 2013)
This paper describes the file of the mandible, the apices of the maxillae, the rupturing device on the maxillae, and the internal structures of the mouthparts in sixty representatives of the nepomorphan families (Heteroptera), using scanning electron microscopy. Eight morphologically distinct types of files are identified on the mandibular tip, as well as six distinct types of the maxillary endings, and three distinct types of rupturing devices of the maxillae. The features of the internal maxillary and mandibular structures share a common connection model, differing only by virtue of specific appendages in different subfamilies. The water bugs morphological ground plan is represented by a mandibular file identically serrated, asymmetrical apices of maxillae (left maxilla tapers with lobe + right maxilla tapers and straight), rupturing device evidently exposed ventrally and inner structures: the maxillae are extended dorso-laterally, forming a wide lobe; symmetrical processes connect with the mandibles. The main patterns (belostomatid and nepid) together with two more specialized patterns (gelastocorids, corixids, micronectids, and diaprepocorids) and (ochterid, aphelocheirid, naucorid, notonectid, pleid and helotrephid) are reported. Diversity of the elements (maxillae and mandibles) are analyzed from a phylogenetic signals and nutrition perspective. Finally, further lines of study are suggested for future work on the phylogeny of the group based on the studied characters.